The legitimacy and governance of Norway's sovereign wealth fund: The ethics of global investment. - Clark, G; Monk, A (Pion Ltd., 2010)
The Norwegian Government Pension Fund-Global is one of the world's largest sovereign wealth funds and is one of the most transparent institutions of its kind. It also has an explicit mission aimed at integrating long-term investment with a two-sided ethical commitment: to corporate engagement according to accepted global principles of best-practice corporate governance, and to ensuring that the fund is not associated with companies that pose a risk to global social and environmental justice. As such, the Norwegian fund has an ethical mandate-something remarkable when compared with other sovereign wealth funds. In this paper we argue that this mission is best understood in terms of procedural, rather than substantive, justice. Our argument is sustained by reference to recent work on the nature of state authority and legitimacy in democratic societies, the logic of institutional governance, and the functional integration of decision making. The paper focuses on the nature and significance of the recommendations from the advisory Council of Ethics and the exercise of powers related to standards of corporate governance. Implications are drawn for understanding the functional performance of the fund in the context of changing global financial markets.